2019
DOI: 10.1038/s41598-019-52549-z
|View full text |Cite
|
Sign up to set email alerts
|

Rectal swabs are a reliable proxy for faecal samples in infant gut microbiota research based on 16S-rRNA sequencing

Abstract: Rectal swabs are potentially a valuable method for monitoring the gut microbiome in research and clinical settings, where it is important to adhere to strict timing, or where acute sampling is needed. It is currently unknown whether rectal swabs give comparable results to faecal samples regarding microbiota community composition in neonates and infants. To study how well the two sampling methods correlate in infants, we compared the 16S-rRNA-based sequencing results of 131 paired rectal swabs and faecal sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 30 publications
1
35
2
Order By: Relevance
“…Currently, feces or mucosal biopsy specimens are the biological samples most commonly used for standard 16S analysis [ 33 ]. However, as shown in several studies, stool and rectal swab are highly similar, indicating that these sampling methods could be used interchangeably to assess the community structure of the distal GI tract [ 34 , 35 ]. Finally, no data on the molecular detection of SARS-CoV-2 in rectal swabs are presented in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, feces or mucosal biopsy specimens are the biological samples most commonly used for standard 16S analysis [ 33 ]. However, as shown in several studies, stool and rectal swab are highly similar, indicating that these sampling methods could be used interchangeably to assess the community structure of the distal GI tract [ 34 , 35 ]. Finally, no data on the molecular detection of SARS-CoV-2 in rectal swabs are presented in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed that bacterial communities defined from endorectal swabbing and stool specimens are similar. 37,38 In addition, we used an enrichment step that allows the recovery of Kp isolates even when the amount of starting material is low, which could potentially be the case when using rectal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…We used rectal swabs rather than fecal samples as a proxy for the gut microbiome, because rectal swabs could be more reliably collected from all of the individuals in our study. Rectal swabs and fecal samples from the same individual have been shown to be very similar and even interchangeable for inferring gut microbial composition with 16S sequencing [ 101 103 ].…”
Section: Methodsmentioning
confidence: 99%